WRITER'S CRAMP: A HISTORICAL REVIEW - O. A. Shavlovskaya (Сеченовский вестник, 2012)
This paper is a review of researches on the mechanisms of hand muscle dystonia the example of which is writer's cramp (WC). WC is a movement disorder — specific kind of dystonia characterized by excessive involuntary muscle contractions, which lead to the formation of abnormal posture during the execution of motor tasks and elective violations often involving highly precise, repetitive movements. WC pathophysiology remains unclear. A lack of inhibition at different levels of the sensorimotor system is considered as one of the basic mechanisms of muscle dystonia. Directions in the study of causes of muscular dystonia (WC) are provided: genetic and neurophysiological examination (transcranial magnetic stimulation (TMS), evoked motor potential (EMP)), neuroimaging techniques (functional MRI, positron emission tomography, PET, a method of threedimensional video analysis of movement.